Traditional Process of Dates, COVID-19 Pandemic Observation, and Challenges in Sindh: Dates traditional processing techniques, and challenges - Meghwar, Parkash; Shar, Nadeem Asghar; Shaikh, Saghir Ahmed; Baloch, Allah Bux; Kumar, Dileep; Dhanker, Preeti; Depar, Ahsan Ali (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
This study brings to the front the reports on the importance of dates, its local processing, and associated all the challenges in the Thari Mirwah sub-district, Khairpur. A survey was planned to collect data based upon the interviews of local farmers. A questionnaire was structured with a total of 20 respondents (each of 4 per village). The demographic results show that the major proportions of the population under study were male (100 %). A 50 % of them were of an age ranging between 30-50 years. Almost, all the respondents were married, with a literacy rate of 20 %. The analysis showed that the dwellers make use of date fruit at variable stages of maturity and prepare different traditional dishes from the flesh of the fruit. Also, they responded that because of the COVID-19 pandemic, there were observable losses that occurred without any proper attention and influence on a timely harvest and supply chain of date fruit. It is concluded that a strong ethnobotanical relation exists between fruit trees and local dwellers of studied Taluka. Limited studies were conducted about the importance and challenges of date fruit in this area. It is recommended that the consumption of natural fruit with enormous antioxidants may help to trigger effective control over challenging issues of food insecurity or malnutrition, being an indigenous food source for the local population of the studied region.